Robotization, internal migration and rural depopulation in Austria - Bekhtiar, Karim (Department of Economics, Johannes Kepler University of Linz, 2022)
Internal migration flows from rural to urban areas have greatly contributed to population declines in many rural areas across both Europe and the US. At the same time there is mounting evidence for a tight connection between internal migration and shifts in labor demand, with the latter being heavily affected by the rise of automation technologies. Therefore this paper analyzes the effects industrial robotization has had on manufacturing employment and internal migration in Austria during the period 2003-2016, specifically focusing on rural-to-urban migration flows. The results show that robotization has caused significant declines in manufacturing employment to which populations reacted by increased out-migration. This migratory response takes the form of rural-to-urban migration, thereby contributing to population declines in many rural areas in Austria. These rural-to-urban movements are primarily driven by young and medium/low skilled individuals, i.e. those groups that bear the strongest shock incidence.
10419/269916
Keywords: Graue Literatur; Employment; internal migration; robots; rural depopulation